2007
DOI: 10.1124/jpet.106.116665
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Mediated Activation of Large-Conductance Calcium-Activated Potassium Channels Contributes to Mesenteric Vasodilatation in Cirrhotic Rats

Abstract: Large-conductance calcium-activated potassium channels (BK Ca s) are important regulators of arterial tone and represent a mediator of the endogenous vasodilator carbon monoxide (CO). Because an up-regulation of the heme oxygenase (HO)/CO system has been associated with mesenteric vasodilatation of cirrhosis, we analyzed the interactions of BK Ca and of HO/CO in the endothelium-dependent dilatation of mesenteric arteries in ascitic cirrhotic rats. In pressurized mesenteric arteries (diameter, 170 -350 m) of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 42 publications
2
46
0
3
Order By: Relevance
“…However, the results of the experiments using HMOX-2 null mice show that other hypoxia sensing mechanisms exist (38). Although the exact role of modulation of Slo1 BK channels by CO in acute oxygen sensing remains uncertain (38), it is clear that CO does activate Slo1 BK channels and contributes to many other physiological processes, including vasodilation (9,11,(13)(14)(15). The ability of the Slo1 BK channel to directly respond to CO at physiological voltages at low to moderate [Ca 2ϩ ] i via the high-affinity RCK1 Ca 2ϩ sensor further illustrates the channel's remarkable modulatory repertoire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of the experiments using HMOX-2 null mice show that other hypoxia sensing mechanisms exist (38). Although the exact role of modulation of Slo1 BK channels by CO in acute oxygen sensing remains uncertain (38), it is clear that CO does activate Slo1 BK channels and contributes to many other physiological processes, including vasodilation (9,11,(13)(14)(15). The ability of the Slo1 BK channel to directly respond to CO at physiological voltages at low to moderate [Ca 2ϩ ] i via the high-affinity RCK1 Ca 2ϩ sensor further illustrates the channel's remarkable modulatory repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of Slo1 BK channels by CO is physiologically and pathophysiologically important. For example, the stimulatory effect of CO on Slo1 BK channels underlies its well documented vasodilatory effect (9,11,(13)(14)(15), and the use of CO has been suggested as a potential therapeutic strategy against pulmonary hypertension (11). Production of CO by HMOXs requires oxygen (1), and this oxygen dependence raises the possibility that changes in cellular oxygen tension regulate the Slo1 BK channel activity indirectly by regulating the availability of CO (16).…”
mentioning
confidence: 99%
“…In contrast, there is an increased NO drive in the peripheral arterial circulation, especially in the splanchnic bed, that causes vasodilation. Other mediators implicated in the splanchnic arterial vasodilation seen in cirrhosis include carbon monoxide (CO) and endogenous cannabinoids (14,15).…”
Section: Systemic Vascular Resistance and Cardiac Dysfunctionmentioning
confidence: 99%
“…Hyper-expression of HO-1 is particularly relevant in cirrhotic rats with ascites and its function is mediated by large-conductance calcium-activated potassium channels [67] . The alpha subunits of these channels, in particular, are increased in cirrhotic animals and their increase may be mediated by the increased HO-1 [68] . In experimental pre-hepatic portal hypertension, obtained by partial portal vein ligation in rats, Fernandez et al [69] have shown that HO activity is increased in the liver.…”
Section: Cirrhotic and Pre-hepatic Portal Hypertensionmentioning
confidence: 99%